Effect of particle size distribution on dynamic properties of cemented coral sand under SHPB impact loading. Issue 162 (November 2022) - Xu, Dongsheng; Zhang, Zhijie; Qin, Yue; Liu, Tao; Cheng, Zhuang
Abstract: The impact mechanical behavior of cemented coral sand is closely related to the particle size of coral sand. This study examined the effects of particle size distribution (PSD) on the impact resistance of cemented coral sand based on the Split-Hopkinson pressure bar (SHPB) tests and discrete element method (DEM). A series of cemented coral sand specimens of different gradations were prepared. Meanwhile, 3D DEM simulations were established and validated by comparing the calculated stress-strain results with the experimental results. The results suggested that the cemented coral sand experienced a sharp increase followed by a gradual decrease of impact resistance with the increase of average particle size d 50 and uniformity coefficient C u . The cemented coral sand with different gradations had dramatically different force-transmission mechanism and failure patterns. The cement matrix and coral sand particles provided the strength together for cemented coral sand when the particles were evenly distributed. The strength decreased when particle breakage occurred and the force-transmission mechanism changed, which also led to uneven PSD. A statistical model was established to predict the peak stress of cemented coral sand according to d 50 and C u based on DEM, which was useful to the optimal design of cemented coral sand in engineering applications. Highlights: Coral sand cement specimens with various gradations are prepared. Study effect of particle size distribution on the impact mechanical properties. Study micromechanical mechanisms by simulating SHPB tests with 3D DEM simulation. Establish a statistical model of predicting peak stress of cemented coral sand.